KUALITAS PEMIMPIN DAN PERUBAHAN SISTEM HUKUM NASIONAL: PERSPEKTIF HUKUM ISLAM DALAM TINJAUAN TEORITIS - M. Iqbal, Lc., M.Ag; Roma Nanda Girsang; Agustrio Mahanggana Angkat; Ananda Viranda; Auliya Putri Riski; Kevin Andreas Halomoan Tambunan; Nabila Fri Cahyani; Philip Marchello Hasonangan Sinaga; Putri Paulina Sembiring; Ridha Nababan; Rimma Annisa Siagihan; Rio Onasis Pangaribuan; Roslin Naiborhu; Sintia Harianti; Tasya Ananda Putri Harahap (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research discusses/describes the Quality of Leadership and the Changes in the National Legal System: An Islamic Law Perspective in Theoretical Review. The success of a nation in organizing its legal system is not only determined by formal aspects such as legislation and institutions but is also significantly influenced by the quality of leadership that guides the direction of legal development. The transformation of Islamic law within the national legal system is a structural and cultural effort to achieve an ideal legal order that meets the needs of the nation (Qomariyah, 2015). The research method used in this study is qualitative with a literature review approach. The data collection technique utilized in this research is library research. Based on this research, the researcher finds that the quality of leadership plays a crucial role in implementing effective changes in the national legal system, where every policy must consider the long-term impacts. Based on this research, the researcher found that the quality of leaders plays an important role in implementing effective changes to the national legal system, where every policy must consider the long-term impact on society.